Effect of planting methods on growth and yield of cassava (Manihot esculenta Crantz) grown with polythene-covering - Abdullahi, N.; Bujang, Japar Sidik; Ahmed, Osumanu Haruna; Zakaria @ Ya, Muta Harah (Horizon Publisher, 2014)
Cassava and Sago constitute the main sources of starch in South East Asia. The production of these starchy plants is in declining due to the problem of low yield, high labor cost, pest and diseases damage, and shortage of land. These production bottlenecks forced Malaysia to import cassava roots from neighboring producer countries. One simple method to enhance cassava productivity is incorporating polythene-covering in agriculture. Present research was carried out to reveal information on the effect of planting methods on some yield attributes in cassava grown with polythene-covering. The involving factors are three cassava varieties, three planting methods, and four black polythene-covering types. The planting methods evaluated were: (і) vertical planting forming 900 angles with ridges, (іі) incline planting forming 450 to 600 angles with ridges, and (ііі) horizontal planting forming 1800 angles with ridges. Significant differences among planting methods in all variables tested were observed. Horizontal and incline plantings were the most efficient in terms of leaf longevity with leaf fall reduction of 49.17% as compared to vertical planting. However, vertical planting recorded the maximum leaf area index of 3.73 per plant. The mean storage roots number of 17.44 per plant obtained in incline planting was the highest. Regardless of variety, the effect of incline planting in terms of fresh storage roots yield was the highest (yields of 20.12 to 32.99 t ha-1). This investigation suggests that storage roots yield of cassava could be enhanced by planting cuttings in an incline position with polythene-covering. Farmers interested in vertical planting could incorporate polythene-covering at day 1 after planting.